Ventanas de Manhattan: una reflexión metacultural - Rodríguez-Mansilla, Fernando (Verbum – Analecta Neolatina, 2006)
The paper considers Antonio Muñoz Molina’s novel, Ventanas de Manhattan, and regards it as a reflection on culture. First, the structure of the novel is inspired by the topic of the "window" and the style of writing, basically description, conforms to an "art of looking" based on the narrator’s habit of looking at art, which is considered to be one of the finest expressions of culture. In other respects, this narrative poetics fails when the narrator attempts to provide a description of the current reality of New York. This failure, a crisis of representation, is provoked, at the time, by a crisis of culture: the contemporary world does not harmonize culture as "art" with culture as a "way of life." New York appears in the book as a modern Babylon, where the narratorprotagonist seeks his identity and judges the way the world goes.